Breastfeeding, HIV exposure, childhood obesity, and prehypertension: A South African cohort study. - Brian Houle; Tamsen J Rochat; Marie-Louise Newell; Alan Stein; Ruth M Bland (PLoS Medicine)
Background Evidence on the association between breastfeeding and later childhood obesity and blood pressure (BP) is inconsistent, especially in HIV-prevalent areas where, until recently, HIV-infected women were discouraged from breastfeeding, but obesity is increasingly prevalent. Methods and findings The Siyakhula cohort (2012-2014), a population-based prospective cohort study, collected data over 3 visits on HIV-negative children ages 7 to 11 years in rural South Africa. We used weight (body mass index [BMI]), fat, and BP as outcome variables and incorporated early life (including mother's age at delivery and HIV status) and current life factors (including maternal education and current BMI). Our primary exposure was breastfeeding duration. We dichotomized 3 outcome measures using pre-established thresholds for clinical interpretability: (1) overfat: ≥85th percentile of body fat; (2) overweight: >1 SD BMI z score; and (3) prehypertension: ≥90th percentile for systolic BP (SBP) or diastolic BP (DBP). We modelled each outcome using multivariable logistic regression, including stopping breastfeeding, then early life, and finally current life factors. Of 1,536 children (mean age = 9.3 years; 872 girls; 664 boys), 7% were overfat, 13.2% overweight, and 9.1% prehypertensive. Over half (60%) of the mothers reported continued breastfeeding for 12+ months. In multivariable analyses, continued breastfeeding between 6 and 11 months was associated with approximately halved odds of both being overfat (adjusted odds ratio [aOR] = 0.43, 95% confidence interval [CI] 0.21-0.91, P = 0.027) and overweight (aOR = 0.46, CI 0.26-0.82, P = 0.0083), but the association with prehypertension did not reach statistical significance (aOR = 0.72, CI 0.38-1.37, P = 0.32). Children with a mother who was currently obese were 5 times more likely (aOR = 5.02, CI 2.47-10.20, P < 0.001) to be overfat and over 4 times more likely to be overweight (aOR = 4.33, CI 2.65-7.09, P < 0.001) than children with normal weight mothers. Differences between HIV-exposed and unexposed children on any of the outcomes were minimal and not significant. The main study limitation was that duration of breastfeeding was based on maternal recall. Conclusions To our knowledge, this is the first study examining and quantifying the association between breastfeeding and childhood obesity in an African setting with high HIV prevalence. We observed that breastfeeding was independently associated with reduced childhood obesity for both HIV-exposed and unexposed children, suggesting that promoting optimal nutrition throughout the life course, starting with continued breastfeeding, may be critical to tackling the growing obesity epidemic. In the era of widespread effective antiretroviral treatment for HIV-infected women for life, these data further support the recommendation of breastfeeding for all women.